Manajemen Sekolah pada Kurikulum Sekolah Penggerak di Sekolah Menengah Kejuruan - Triati, Triati; Jalinus, Nizwardi; Ridwan, Ridwan (Universitas Negeri Padang, 2022)
This study aims to describe the process of secondary school-based management in the “Sekolah Penggerak”curriculum. The research method used is a qualitative description. Data collection techniques were carried out by means of interviews, direct observation and documentation. The results of the study describe a “Sekolah Penggerak”program that focuses on developing student learning outcomes holistically by realizing the Pancasila Student Profile which includes competence and character starting with superior human resources.